Pathogenesis of Disorders of the Motor Function of the Large Intestine in Functional Constipation - M. M. Galagudza; Yu. P. Uspensky; Yu. A. Fominykh; D. Yu. Butko (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
Aim: to analyze the scientific literature on the role of various factors in the mechanisms of development of functional constipation and to summarize the current data on its leading pathogenetic mechanisms.Key points. Constipation occurs in 15 % of the adult population in the world and leads to a significant decrease in the quality of life, and in combination with some other symptoms may indicate the presence of an organic pathology of the gastrointestinal tract. The pathogenetic basis of functional constipation (FC) with slow intestinal transit is a decrease in colonic motor function, which is confirmed by the results of high-resolution manometry. FC is characterized by disturbances in such motor patterns of the colon as low and high amplitude propagating contractions, segmental non-propagating contractions, and general increases in pressure. The main FC mechanisms associated with neurogenic dysregulation include impaired function of the gray and white matter of the brain, as well as an increase in the tone of the sympathetic nervous system with a concomitant decrease in the influence of cholinergic nerves innervating the large intestine. A key role in the FC development belongs to a decrease in the pool of interstitial cells, which play the role of an intestinal pacemaker, due to slowing of their self-renewal. FC-associated changes in the enteric nervous system include a relative excess of the contribution of inhibitory influences and a decrease in the activity of cholinergic and serotonergic neurons that stimulate intestinal motility. A certain role in the occurrence of reduced motor function of the colon may have an imbalance in the production of intestinal hormones synthesized by enteroendocrine cells, namely, a deficiency of motility stimulants, which include motilin, gastrin, ghrelin and cholecystokinin, as well as a relative excess of hormones that suppress motility (somatostatin and vasoactive intestinal polypeptide). Changes in the composition of the intestinal microbiota can also contribute to the FC occurrence, which is associated with a dysfunction of the metabolite profile produced by intestinal bacteria.Conclusions. Functional constipation is a classic multifactorial disease, in the etiology of which the adverse effects of the genotype are combined with multiple acquired risk factors. A more complete understanding of the molecular mechanisms of the FC development can serve as the basis for the emergence of new effective treatments for this common pathology.